2012
DOI: 10.12693/aphyspola.121.23
|View full text |Cite
|
Sign up to set email alerts
|

Bioceramic Production from Sea Urchins

Abstract: Bioceramic nanopowders, currently one of the most demanding challenges for producing new biomaterials, have been tackled only when starting from chemical reagents. There are few studies aiming at producing hydroxyapatite nanopowders from naturally derived raw materials, such as nacre shells. Natural species of sea origin, such as corals and nacres, always attract special interest in biomaterials science and technology. Nacre shells are made up of pure aragonite crystallized in an organic matrix. The most commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Interplay of one form of CaCO 3 to other form reported in many animals. For instance, nacre shells purely made up of aragonite crystal and they can transform to hydroxyapatite by hydrothermal transformation in high pressure ( Agaogullari, 2012 ). Sea urchins have complex skeletal structure; though inter-relation among amorphous calcium carbonate, calcite and intra-crystalline organics is not clear; the biomineralization process in sea urchin is well documented where the transient form of hydrated ACC dehydrates to form ACC and subsequently transformed to calcite ( Wolpert and Gustafson 1961 ; Brecevic and Nielsen 1989 ; Clarkson et al., 1992 ; Beniash et al., 1997 ; Decker et al., 1987 ; Yutao Gong et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interplay of one form of CaCO 3 to other form reported in many animals. For instance, nacre shells purely made up of aragonite crystal and they can transform to hydroxyapatite by hydrothermal transformation in high pressure ( Agaogullari, 2012 ). Sea urchins have complex skeletal structure; though inter-relation among amorphous calcium carbonate, calcite and intra-crystalline organics is not clear; the biomineralization process in sea urchin is well documented where the transient form of hydrated ACC dehydrates to form ACC and subsequently transformed to calcite ( Wolpert and Gustafson 1961 ; Brecevic and Nielsen 1989 ; Clarkson et al., 1992 ; Beniash et al., 1997 ; Decker et al., 1987 ; Yutao Gong et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vecchio et al performed a classic hydrothermal conversion process from sea urchin spines into TCP. The obtained products exhibited good bioactivity and osteoconductivity [ 145 ]. Researchers demonstrated that rod-shaped HA crystals are favored in the attachment of proteins, especially in the binding of vitamin D, applied in BTE, due to its strong adhesion to osteoclasts and similarity with the native HA structure.…”
Section: Ha-based On Natural Sources Used In Btementioning
confidence: 99%
“…In addition to Mg, numerous other co-precipitated elements are differentially incorporated into biotic calcitic structures such as phosphorus (P; e.g., calcium phosphate) and strontium (Sr; e.g., strontium calcite) (Mackenzie et al, 1983). Some trace metals, such as iron (Fe) and zinc (Zn), have been found to enhance mechanical properties of biomineralized structures (e.g., iron oxides, zinc oxides), and inspire the development of anthropogenic biomaterials (Meyers et al, 2008;Agaogullari et al, 2012;Naleway et al, 2016).…”
Section: Introductionmentioning
confidence: 99%